Spontaneously Hypertensive Rats (SHR) Are Resistant to a Reserpine-Induced Progressive Model of Parkinson’s Disease: Differences in Motor Behavior, Tyrosine Hydroxylase and α-Synuclein Expression - Leão, Anderson H. F. F.; Meurer, Ywlliane S. R.; da Silva, Anatildes F.; Medeiros, André M.; Campêlo, Clarissa L. C.; Abílio, Vanessa C.; Engelberth, Rovena C. G. K.; Cavalcante, Jeferson S.; Izídio, Geison S.; Ribeiro, Alessandra M.; Silva, Regina H. (Frontiers in Aging Neuroscience, 2017)
Reserpine is an irreversible inhibitor of VMAT2 used to study Parkinson’s disease (PD) and screening for antiparkinsonian treatments in rodents. Recently, the repeated treatment with a low-dose of reserpine was proposed as a progressive model of PD. Rats under this treatment show progressive catalepsy behavior, oral movements and spontaneous motor activity decrement. In parallel, compared to Wistar rats, spontaneously hypertensive rats (SHR) are resistant to acute reserpine-induced oral dyskinesia. We aimed to assess whether SHR would present differential susceptibility to repeated reserpine-induced deficits in the progressive model of PD. Male Wistar and SHR rats were administered 15 s.c. injections of reserpine (0.1 mg/kg) or vehicle, every other day and motor activity was assessed by the catalepsy, oral movements and open field tests. Only reserpine-treated Wistar rats presented increased latency to step down in the catalepsy test and impaired spontaneous activity in the open field. On the other hand, there was an increase in oral movements in both reserpine-treated strains, although with reduced magnitude and latency to instauration in SHR. After a 15-day withdrawn period, both strains recovered from motor impairment, but SHR animals expressed reduced latencies to reach control levels. Finally, we performed immunohistochemistry for tyrosine hydroxylase (TH) and α-synuclein (α-syn) 48h after the last injection or 15 days after withdrawn. Reserpine-treated animals presented a reduction in TH and an increase in α-syn immunoreactivity in the substantia nigra and dorsal striatum, which were both recovered after 15 days of withdraw. Furthermore, SHR rats were resistant to reserpine-induced TH decrement in the substantia nigra, and presented reduced immunoreactivity to α-syn in the dorsal striatum relative to Wistar rats, irrespective of treatment. This effect was accompanied by increase of malondaldhyde (MDA) in the striatum of reserpine-treated Wistar rats, while SHR presented reduced MDA in both control and reserpine conditions relative to Wistar strain. In conclusion, the current results show that SHR are resilient to motor and neurochemical impairments induced by the repeated low-dose reserpine protocol. These findings indicate that the neurochemical, molecular and genetic differences in the SHR strain are potential relevant targets to the study of susceptibility to PD.